Cape Cod Stories - Lincoln, Joseph Crosby, 1870-1944 (Salt Lake City, UT : Project Gutenberg, 2006)
"Cape Cod Stories" by Joseph Crosby Lincoln is a collection of short stories written during the early 20th century. The book paints vivid portraits of life on Cape Cod, focusing on the experiences and quirks of its local characters, including Cap'n Jonadab Wixon and Barzilla Wingate. Through their adventures and encounters, the stories explore themes of friendship, social class, and the contrast between rural simplicity and urban sophistication. The opening of the collection introduces readers to Cap'n Jonadab and Barzilla as they visit the post office and receive unexpected wedding invitations, which sets the stage for their upcoming journey. As they prepare to attend the wedding of a friend's daughter, readers are treated to their humorous banter and observations about the social expectations that come with such events. This establishes the tone for the stories to follow, which often blend comedy with commentary on the lives of the characters as they navigate various situations unique to their coastal town. Through clever dialogue and relatable experiences, Lincoln invites readers to immerse themselves in the charm and peculiarities of Cape Cod life. (This is an automatically generated summary.)
Two pairs of shoes -- The count and the manager -- The south shore weather bureau -- The dog star -- The mare and the motor -- The mark on the door -- The love of Lobelia 'Ankins -- The meanness of Rosy -- The antiquers -- His native heath -- Jonesy.
Also published under the title "The Old Home House"
Release date is 2006-06-06
Don Lainson; David Widger
Keywords: Short stories, American; Cape Cod (Mass.) -- Fiction